Combined effect of gamma-radiation and pH on corrosion of Ni–Cr–Fe alloy inconel 600. (August 2016) - Musa, A.Y.; Wren, J.C.
Highlights: Corrosion of Inconel 600 involves mainly Fe and Ni oxidation with minimal Cr oxidation. Metal oxidation leads to two competing processes, oxide growth and dissolution. Gamma-radiation increases the Fe and Ni oxidation rates, but its effect varies with pH. Increased oxidation leads preferentially to oxide growth at pH25 °C 10.6. Increased oxidation leads preferentially to dissolution at pH25 °C 6.0. Abstract: The effect of γ-radiation on the corrosion of Ni–Cr–Fe alloy Inconel 600 was studied at pH25 °C 6.0, 8.4 and 10.6 at 150 °C by analyzing both the corroded surfaces and dissolved metal loss. Exposed to γ-radiation water decomposes to a range of redox active species. This increases the metal oxidation rate initially, but the consequence of this increase varies with pH. At pH25 °C 10.6 where the solubilities of Fe II and Ni II are near their minima, the increase in metal oxidation rate mostly increases solid oxide/hydroxide growth. At a lower pH it increases metal ion dissolution more.